Contesting Religious Authority in the Post-Truth Era through a Case Study of Fatwas Issued by the Indonesian Ulema Council and Online Preachers - Zayyadi, Ahmad; Hasan, Zainol; Kasrim, Kasrim (Westscience Press, 2025)
This study explores the transformation and contestation of religious authority in Indonesia’s post-truth era through a qualitative case study of fatwas issued by the Indonesian Ulema Council (MUI) and the interpretive narratives of online preachers. The post-truth era—where emotion and personal belief often overshadow factual or scholarly legitimacy—poses unique challenges to institutional religious bodies. Utilizing a qualitative approach with in-depth interviews of three informants—an MUI fatwa commission member, an online preacher, and a Muslim academic—this research investigates how authority, authenticity, and credibility are constructed, perceived, and contested in the digital age. The findings reveal that MUI continues to maintain doctrinal legitimacy through its procedural and scholarly rigor, yet it struggles to compete with the affective appeal and immediacy of online religious influencers. Online preachers, empowered by digital platforms, reshape religious discourse through personalization, storytelling, and interactivity, often appealing to emotion rather than jurisprudential authority. Meanwhile, academics view this transformation as both an opportunity for religious democratization and a challenge to theological coherence. The study concludes that religious authority in Indonesia is shifting from institutional centralization to networked pluralism, where credibility is negotiated between traditional expertise and popular visibility. This shift calls for a renewed ethical and communicative framework that bridges scholarly authenticity with digital accessibility in order to preserve the integrity of Islamic knowledge in the post-truth era.